2009
DOI: 10.1001/archsurg.2009.81
|View full text |Cite
|
Sign up to set email alerts
|

Portomesenteric Venous Thrombosis After Laparoscopic Surgery

Abstract: Portomesenteric venous thrombosis following laparoscopic surgery usually manifests as nonspecific abdominal pain. Computed tomography can readily provide the diagnosis and demonstrate the extent of the disease. Treatment should be individualized based on the extent of thrombosis and the presence of bowel ischemia but should include anticoagulation therapy. Venous stasis from increased intra-abdominal pressure, intraoperative manipulation of splanchnic vasculature, and systemic thrombophilic states likely conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
153
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 75 publications
5
153
1
7
Order By: Relevance
“…This decrease in venous flow varies from 35 % to 84 %. Insufflation with carbon dioxide induces a more substantial decrease in venous flow than with other inert gases [2,3]. This study revealed no significant difference in the incidence of PMVT between laparoscopic and open surgeries in cases of EGC.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…This decrease in venous flow varies from 35 % to 84 %. Insufflation with carbon dioxide induces a more substantial decrease in venous flow than with other inert gases [2,3]. This study revealed no significant difference in the incidence of PMVT between laparoscopic and open surgeries in cases of EGC.…”
Section: Discussionmentioning
confidence: 50%
“…Prompt initiation of anticoagulation therapy is the current recommendation for the treatment of acute PMVT [2]. Previous studies recommended a 6-to 12-month period of anticoagulation therapy [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations